Projected Impact of Weight Gain During the COVID-19 Pandemic on the Future Burden of Cancer in Canada - Murphy, Rachel A.; Parks, Jaclyn; Woods, Ryan; Brenner, Darren R.; Ruan, Yibing; Bhatti, Parveen (Frontiers in Oncology, 2022)
The COVID-19 pandemic and resulting public health measures have had significant impacts on daily life, including shifts in health behaviours which contribute to weight gain and may increase subsequent risk of chronic diseases such as cancer. Using OncoSim, a web-based microsimulation tool, we estimated the future burden of cancer in Canada by incorporating data on unintentional weight gain among adults during the first year of the COVID-19 pandemic. Population impact measures were estimated until 2042, assuming a 12-year latency period. We estimated 12,160 excess cancer cases and 4,567 excess cancer deaths by 2042 due to COVID-19 related weight gain. The largest estimated impacts were observed for endometrial, kidney and liver cancers among women, with potential impact fractions (PIF) of 2.87%, 1.67% and 1.30%, respectively. For men, the largest mean PIFs were observed for esophageal (2.48%), kidney (1.85%) and liver (1.47%) cancers. Changes in health behavior during the COVID-19 pandemic are likely to have significant and long-lasting impacts on cancer burden. These projections highlight the immediate need for investment into the development and implementation of effective cancer prevention strategies.